Probiotics Fermented Bitter Melon Juice as Promising Complementary Agent for Diabetes Type 2: Study on Animal Model - Laksmi Hartajanie; S. Fatimah-Muis; K. Heri-Nugroho HS; Ign Riwanto; M. Sulchan (Journal of Nutrition and Metabolism)
Background and Aim. Bitter melon (Momordica charantia/MC) contains charantin that has antidiabetic properties as an α-glucosidase inhibitor and antioxidative properties. Lactic acid fermentation using Lactobacillus fermentum LLB3 increased its antioxidative properties. The study was aimed to analyse the difference of the treatment that influences blood glucose and SOD level before and after treatment compared to acarbose. Experimental procedure. A total of 24 male Sprague-Dawley rats were used. Diabetes type 2 was induced by a single dose (60 mg/kg) of streptozotocin (STZ) and 120 mg/kg of nicotinamide, intraperitoneally. Following three days of STZ induction, the animals were randomly divided into four groups. Groups 1, 2, 3, and 4 were given acarbose 40 mg/100 g feed, MC 10 ml/kg body weight, fermented MC 10 ml/kg body weight, and distilled water, respectively, for 28 days. Glucose and SOD values were measured by spectrophotometer and ELISA, respectively. The difference between pretest and posttest data was analysed using the pair t-test. Data were analysed using ANOVA and Tukey HSD for post hoc analysis. Level of significance was set at 0.05. Results. Fasting glucose and postprandial blood glucose were significantly decreased in groups given MC and fermented MC but not as low as those in the acarbose group (p<0.001). The value of SOD significantly increased in groups given MC and fermented MC but not as high as those in the acarbose groups (p<0.001). Conclusion. Although MC gave significant results in increasing SOD and lowering fasting as well as postprandial blood glucose, fermented MC was better than MC, and acarbose still gave the best results.